2017
DOI: 10.1177/1178623x17694150
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Detection of Intraplaque Hemorrhage

Abstract: Carotid artery atherosclerosis is a major cause of ischemic stroke. For more than 30 years, future stroke risk and carotid stroke etiology have been determined using percent diameter stenosis based on clinical trials in the 1990s. In the past 10 years, magnetic resonance imaging (MRI) sequences have been developed to detect carotid intraplaque hemorrhage. By detecting carotid intraplaque hemorrhage, MRI identifies potential stroke sources that are often overlooked by lumen imaging. In addition, MRI can dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 118 publications
(152 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, it is a factor predisposing for a recurrent cerebral ischaemic episode [48]. Upon MRI imaging [49] IPH is more often revealed in symptomatic patients [47,50]. Abnormal vessels formed during neovascularization may rupture spontaneously or may lead to chronic intraplaque haemorrhage.…”
Section: Atherosclerotic Plaque Instabilitymentioning
confidence: 99%
“…Furthermore, it is a factor predisposing for a recurrent cerebral ischaemic episode [48]. Upon MRI imaging [49] IPH is more often revealed in symptomatic patients [47,50]. Abnormal vessels formed during neovascularization may rupture spontaneously or may lead to chronic intraplaque haemorrhage.…”
Section: Atherosclerotic Plaque Instabilitymentioning
confidence: 99%
“…Furthermore,Kerwin et al showed that K trans in the carotid adventitia in the presence of plaques provides a quantitative proxy for the extent of VVn(55,56). DCE-MRI can be used to estimate arterial and plaque calcification, loosening of the matrix, or haemorrhages, by measuring the response to a variety of magnetic pulses(53,54,69,70). The ability of DCE-MRI to measure these characteristics of the atherosclerotic plaque allows the identification of high-risk plaques (71-73) and opened new uses for the technique.…”
mentioning
confidence: 99%
“…10,50 Scoring of IPH using MR imaging has proven to be an accurate method to identify IPH and has been validated with histopathology by us and others (specificity >86%, sensitivity ≥80%). 51,52 Although manual quantification of IPH is a laborious procedure, we have demonstrated high inter-observer agreement values (ĸ=0.95). 34 The degradation of hemorrhage into methemoglobin results in T1 shortening and, correspondingly, causes a high signal intensity on T1-weighted (T1w) MR images.…”
Section: Mri As An Imaging Marker For Risk Predictionmentioning
confidence: 70%
“…50 Thirdly, computational models have shown IPH to be associated with higher structural wall stress. 51 Finally, a recent study from Lin et al showed an association between IPH and plaque surface calcification, 52 that has been shown to lead to a local increase in biomechanical stress. 53 Apart from a lower vessel wall K trans , presence of IPH was positively associated with NWI (indicative for plaque burden).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation